Preventing interface damage by pre-conditioning polymer-coated steels via rolling. (April 2015) - van Beeck, J.; van Breemen, L.C.A.; Schreurs, P.J.G.; Geers, M.G.D.
Abstract: A novel methodology is presented for pre-conditioning a polymer-coated steel used in food and beverage packaging. Mechanical rejuvenation of the coating via rolling is studied in order to prevent interface damage in subsequent forming operations. The simulations reveal that the thermodynamic state of the polymer coating after rolling depends on the rolling reduction. This dependency can be used to tailor the thermodynamic state of the coating prior to can production. A proof-of-principle simulation was performed to study the effects of rejuvenation on subsequent deformation processes. Deformation-induced interface roughening was studied for the initial and rejuvenated polymer coating. The predictions for a rejuvenated polymer coating indicate a significant decrease in interface damage. The presented numerical framework allows for a detailed study of the effects of pre-conditioning on the interface integrity during subsequent forming operations. With properly identified material parameters, it becomes possible to tailor the polymer–steel material properties before and during production to minimize interface damage during production and storage of cans or canisters, e.g. for food and beverage packaging.